2006
DOI: 10.1063/1.2390645
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence oscillations in porous alumina films

Abstract: The dominant oscillation shown in the laser-excited photoluminescence spectrum of the porous alumina film can be ascribed to the interference within a Fabry-Pérot optical cavity where the separation between two neighboring oscillations is highly sensitive to the film’s thickness and refractive index. The method, designated as photoluminescence oscillation, endows photoluminescence spectrum with another dimension and results in a nondestructive method for the measurement of the thickness and refractive index wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Up to now, the PL nature of different emissions is still ambiguous though most of reports have tentatively attributed them to F + and F centers, related to oxygen vacancy defects, as well as, to oxalic impurities (especially light elements) [25,26]. Small superimposed oscillations that appear on the PL curves could be associated with interference effects like Huang et al recently published [27]. In contrast to γ--alumina nanoparticles [28], here under ultraviolet excitation (λ exc = 244 nm with a power density of 10 3 W/cm 2 ) there is no induced degradation in the PL intensity of low energy bands.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, the PL nature of different emissions is still ambiguous though most of reports have tentatively attributed them to F + and F centers, related to oxygen vacancy defects, as well as, to oxalic impurities (especially light elements) [25,26]. Small superimposed oscillations that appear on the PL curves could be associated with interference effects like Huang et al recently published [27]. In contrast to γ--alumina nanoparticles [28], here under ultraviolet excitation (λ exc = 244 nm with a power density of 10 3 W/cm 2 ) there is no induced degradation in the PL intensity of low energy bands.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have pointed out that the PL spectrum of NAA presents oscillations generated by the Fabry-Pérot effect. [11] The number, intensity and position of those oscillations rely on the NAA thickness (i.e., the pore length). In preliminary experiments, we have observed that these oscillations are related to the pore diameter too.…”
Section: Doi: 101002/adma201104490mentioning
confidence: 99%
“…Huang et al reported that thin porous AAOs can act as a Fabry-Pérot optical cavity constituted by the air-AAO-Al, producing oscillating reflectance and PL spectra due to multiple-reflection interferences of the propagating waves [121]. From the fact that the band gap of alumina is much bigger than the photon energy of the considered PL spectral range (typically, 2.25-3.54 eV) and the absorption coefficient is very small, the authors deduced the optical thickness (2nL AAO ) of porous AAOs [121]:…”
Section: Pore Wideningmentioning
confidence: 99%